Better technology for African farmers - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
Resource-poor African farmers are being given the chance to grow high-yielding crops, thanks to an initiative by the African Agricultural Technology Foundation (AATF), which links small-scale producers up with technological solutions for agriculture.